Eosinophilic cholecystitis: a rare cause of acute cholecystitis 'case report' - Abdulkarim Hasan; Khalid Nafie (Wolters Kluwer Medknow Publications, 2019)
We report two cases of eosinophilic acute cholecystitis in two male patients aged 43 and 20 years without peripheral eosinophilia.